A new and extraordinary cyrtochilum (orchidaceae: oncidiinae) from Colombia - Giraldo, Giovanny (2013)
A new species of Cyrtochilum from Antioquia, Colombia, is described and illustrated, and compared with the similar Ecuadorian C. cryptocopis and C. trifurcatum, but differs in having a different ventral structure and much narrower wings of the column, and also by the much broader frontlobe of the lip.